2017
DOI: 10.1371/journal.pone.0179977
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar anodal tDCS increases implicit learning when strategic re-aiming is suppressed in sensorimotor adaptation

Abstract: Neurophysiological and neuroimaging work suggests that the cerebellum is critically involved in sensorimotor adaptation. Changes in cerebellar function alter behaviour when compensating for sensorimotor perturbations, as shown by non-invasive stimulation of the cerebellum and studies involving patients with cerebellar degeneration. It is known, however, that behavioural responses to sensorimotor perturbations reflect both explicit processes (such as volitional aiming to one side of a target to counteract a rot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 83 publications
3
19
1
Order By: Relevance
“…Although participants showed a clear ability to adapt to the novel visuomotor rotation, the expected significant enhancement of adaptation by anodal cerebellar tDCS, that had been shown in various studies (Galea et al 2011 ; Hardwick and Celnik 2014 ; Block and Celnik 2013 ; Leow et al 2017 ), was not observed here. Despite our sample size being in the same range of previously published tDCS papers, a recent study indicates this could be significantly under powered (Minarik et al 2016 ).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Although participants showed a clear ability to adapt to the novel visuomotor rotation, the expected significant enhancement of adaptation by anodal cerebellar tDCS, that had been shown in various studies (Galea et al 2011 ; Hardwick and Celnik 2014 ; Block and Celnik 2013 ; Leow et al 2017 ), was not observed here. Despite our sample size being in the same range of previously published tDCS papers, a recent study indicates this could be significantly under powered (Minarik et al 2016 ).…”
Section: Discussioncontrasting
confidence: 53%
“…For instance, Galea et al ( 2011 ) applied anodal cerebellar tDCS during visuomotor adaptation and found anodal cerebellar tDCS led to faster adaptation, relative to either primary motor cortex (M1) anodal tDCS or sham tDCS (Galea et al 2011 ). This effect on motor adaptation/learning has been replicated in visuomotor adaptation (Hardwick and Celnik 2014 ; Block and Celnik 2013 ; Doppelmayr et al 2016 ; Leow et al 2017 ), force-field adaptation (Herzfeld et al 2014 ), locomotor adaptation (Jayaram et al 2012 ), saccade adaptation (Panouilleres et al 2015 ; Avila et al 2015 ), motor skill learning (Cantarero et al 2015 ), and language prediction tasks (Miall et al 2016 ). As a result, it has been suggested that cerebellar tDCS is not only a useful tool to understand cerebellar function but also as a possible clinical technique to restore cerebellar function in patients suffering from cerebellar-based disorders (Grimaldi et al 2014 ).…”
Section: Introductionmentioning
confidence: 79%
“…Saccadic adaptation by contrast is a largely implicit task . The neural correlates of such task‐related differences are complex, but the cerebellum may be preferentially recruited with implicit paradigms that could therefore be important in driving the differences observed in DYT11 . Another alternative is that the saccadic adaptation deficits identify a cerebellar‐independent mechanism that is revealed selectively by testing saccadic adaptation .…”
Section: Discussionmentioning
confidence: 99%
“…10 The neural correlates of such task-related differences are complex, but the cerebellum may be preferentially recruited with implicit paradigms that could therefore be important in driving the differences observed in DYT11. 23,24 Another alternative is that the saccadic adaptation deficits identify a cerebellar-independent mechanism that is revealed selectively by testing saccadic adaptation. 10 Saccadic and limb adaptation are likely to involve overlapping distributed networks, but certain features such as brain stem processing are clearly more important in the control of eye movements.…”
Section: And Selective Deficitsmentioning
confidence: 99%
“…Notably, limiting standard implicit adaptation to a body model does not necessarily contradict the idea that internal models and the cerebellum underlie tool transformations (Imamizu et al 2003;Higuchi et al 2007;Imamizu and Kawato 2009). Recent neuroimaging and patient studies indicate that cerebellum-based internal models support not only the implicit (Leow et al 2017), but also the explicit component of visuomotor adaptation (Werner et al 2014;Butcher et al 2017). A possibility is that internal models support the selection of suitable actions by simulating their hypothetical outcomes (Barsalou 1999).…”
Section: Discussionmentioning
confidence: 99%